Clinical outcomes and impact of prognostic factors in resectable oral cavity squamous cell carcinoma - Shatha Abu Taha; Taher Abu Hejleh; Lina Wahbeh; Abdulla Alzibdeh; Mohammad Berawi; Mohamed Qambar; Mohammad Mukahal; Fawzi Abuhijla; Ramiz Abu-Hijlih; Ayat Taqash; Tariq Hussein; Medyan Alrousan; et al. (Frontiers in Oncology, 2024)
PurposeTo evaluate clinical outcomes and prognostic factors in non-metastatic oral cavity squamous cell carcinoma (OCSCC) patients who underwent surgery with or without adjuvant therapy.MethodsFrom 2007 and 2018, 116 patients were analyzed. The primary endpoint was overall survival (OS), and secondary endpoints were disease-free survival (DFS), local failure (LF), regional failure (RF), and distant metastases (DM). Kaplan-Meier method and log-rank test assessed survival outcomes, while Cox proportional hazard tests analyzed prognostic factors.ResultsMedian patient age was 53 years, most were smokers (93.5%) and males (62.9%). Predominant subsite was the oral tongue (58.6%). Treatment included surgery alone (16.4%), adjuvant radiotherapy (46.6%), or adjuvant concurrent chemoradiotherapy (CCRT) (37%). The median follow-up time was 45.9 months. There were significant differences between groups in terms of gender (P=0.028) and RT dose (P=0.01). The 3-year OS, DFS, LF, RF and DM for the entire cohort were 60.9%, 55.1%, 20.11%, 8.43%, and 17.13%, respectively. Surgery alone yielded higher 3-year OS (81.4%) than adjuvant RT (70%) or adjuvant CCRT (41.4%), (p=0.012). Adjuvant CCRT correlated with higher LF compared to adjuvant RT and surgery alone groups (p=0.029). Lymphovascular invasion (LVI) impacted OS (HR=2.034, p=0.0498) and DM (HR=3.380, p=0.0132), while higher tumor grade increased DM likelihood (HR=8.477, p=0.0379).ConclusionsThis study reports OCSCC patient outcomes in Jordan across different treatment modalities. Adjuvant CCRT correlated with higher LF rates, and LVI impacted OS and DM, aligning with existing OCSCC treatment literature.